2019
DOI: 10.1002/cam4.2143
|View full text |Cite
|
Sign up to set email alerts
|

Systematic evaluation of cancer‐specific genetic risk score for 11 types of cancer in The Cancer Genome Atlas and Electronic Medical Records and Genomics cohorts

Abstract: Background Genetic risk score (GRS) is an odds ratio (OR)‐weighted and population‐standardized method for measuring cumulative effect of multiple risk‐associated single nucleotide polymorphisms (SNPs). We hypothesize that GRS is a valid tool for risk assessment of most common cancers. Methods Utilizing genotype and phenotype data from The Cancer Genome Atlas (TCGA) and Electronic Medical Records and Genomics (eMERGE), we tested 11 cancer‐specific GRSs (bladder, breast, colorectal, glioma, lung, melanoma, ovari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
27
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(28 citation statements)
references
References 112 publications
0
27
0
Order By: Relevance
“…Few pan-cancer PRS studies have been conducted in prospective cohorts and none have considered the breadth of modifiable risk factors that we evaluated. Shi et al 17 tested 11 cancer PRS in cases from The Cancer Genome Atlas and controls from the Electronic Medical Records and Genomics Network. This analysis was limited by fewer risk variants in each PRS, as well as potential for bias due to selection of cases and controls from different populations.…”
Section: Discussionmentioning
confidence: 99%
“…Few pan-cancer PRS studies have been conducted in prospective cohorts and none have considered the breadth of modifiable risk factors that we evaluated. Shi et al 17 tested 11 cancer PRS in cases from The Cancer Genome Atlas and controls from the Electronic Medical Records and Genomics Network. This analysis was limited by fewer risk variants in each PRS, as well as potential for bias due to selection of cases and controls from different populations.…”
Section: Discussionmentioning
confidence: 99%
“…For example, Gu et al built a PRS for melanoma based on their metaanalysis, which reported an AUC of 0.64 (95% CI = 0.63‐0.66) and a 3.33‐fold increased risk when comparing the fifth to the first PRS quintile 27 . For glioma, significant dose‐response associations were observed for higher PRS with higher OR ( P value = 4.49 × 10 −31 ) 28 . For chronic lymphoid leukemia, PRS were strongly associated with disease risk (OR, 3.02; P value = 7.8 × 10 −30 ) and showed high discrimination ability (AUC = 0.78) 29 .…”
Section: Discussionmentioning
confidence: 99%
“…27 For glioma, significant dose-response associations were observed for higher PRS with higher OR (P value = 4.49 × 10 −31 ). 28 For chronic lymphoid leukemia, PRS were strongly associated with disease risk (OR, 3.02;…”
Section: Discussionmentioning
confidence: 99%
“…The degree of overlap in the genetic determinants of cancers has been explored through the examination of the genetic correlations derived from individual GWAS results and data, as well as studies of the pleiotropic effects of individual genetic variants on multiple cancers. (7,18,20,49,50) In addition, many cancers have also been shown to be genetically correlated with non-cancer-related diseases. (24,51) These genetic correlations, possibly exacerbated by relevant environmental factors, are also quite likely to lead to cancer patients developing a second primary cancer (as opposed to recurrent cancers) or have comorbid illness.…”
Section: Discussionmentioning
confidence: 99%